ANALYSIS OF PARTIAL COMMUNITY REJECTION OF THE COMPLETE SYSTEMATIC LAND REGISTRATION PROGRAM WITH COMMUNITY PARTICIPATION (PTSL-PM) - Ali, Moh Fikry; Fathurrohman, Firman; Supriani, Ani; Harmono, Harmono; Solichin, Solichin (Devotion : Journal of Research and Community Service, 2024)
The Ministry of Agrarian Affairs and Spatial Planning/National Land Agency has created a national priority program called the Accelerated Complete Systematic Land Registration (PTSL) as regulated in Ministerial Regulation ATR/BPN No. 6 of 2018. The PTSL program will be implemented throughout the Republic of Indonesia with the aim of accelerating the provision of legal certainty to all land rights holders, thereby helping to prevent land disputes in the community. The research contribution is the identification and analysis of the reasons why some members of the Mundu Pesisir Village community reject the PTFL-PM program. The study found that the response of the community to the program was very positive. However, there are internal family barriers to its implementation. Strategies of the Cirebon Regency Land Office and the Land Data Collector at the Land Office to Ensure the Proper Implementation of the Program are discussed.